Automated Information Guided System (AIGS) to improve orientation accuracy and mobility for students with visual impairment - Efendi, Mohammad; Handayani, Anik Nur; Nazaruddin, M. Arief; Sediono, Wahju; Rizky, R Amalia (IEEE, 2025)
Vision loss significantly impacts individuals' ability to navigate environments and perform daily tasks, particularly in higher education contexts. At the State University of Malang (UM), students with visual impairments face challenges, with a reported 30% experiencing navigation errors or accidents on campus. To enhance mobility and orientation accuracy for these students, this project develops and evaluates the Automated Information Guided System (AIGS), a mobile application that integrates GPS, sensors, audio, and haptic feedback. The Waterfall paradigm was utilized to develop the system through the stages of requirements analysis, design, implementation, testing, and maintenance. Tests with UM visually challenged students using a range of mobile devices show that the AIGS is feasible in terms of usefulness, usability, learning curve, and user satisfaction. These findings suggest that AIGS increases visually impaired students' sense of security and independence while also improving their mobility and orientation accuracy.